Translation, cross-cultural adaptation and validation of the Mandarin version of the BDDQ-AS for rhinoplasty patients - Wilson A. Wijaya; Yu Liu; Min Zhou; Yong Qing; Zhengyong Li (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The BDDQ-AS (Body Dysmorphic Disorder Questionnaire—Aesthetic Surgery) is a simple and reliable patient-reported outcome measure. It can be used as a screening tool for body dysmorphic disorder (BDD) in patients undergoing aesthetic rhinoplasty. The aim of this study was to translate and culturally adapt the Mandarin version of the BDDQ-AS (M-BDDQ-AS) and evaluate its selected psychometric validation in patients after rhinoplasty. Method According to international guidelines, the BDDQ-AS questionnaire was translated from English to Mandarin. Twenty Mandarin-speaking rhinoplasty patients were interviewed in order to evaluate the understandability and acceptability of the translation and produce a final version. It was then administered to 137 patients with a mean age of 38.75 ± 6.24 years. Psychometric validation were evaluated using reliability (internal consistency, test–retest reliability) and item-reponse theory (IRT) test. Result High internal consistency of 0.823 was found using Cronbach’s α coefficient. Reliability of the M-BDDQ-AS resulted in Intraclass Correlation Coefficient (ICC) = 0.863. Besides, based on IRT analysis, the discrimination abilities of all the items were good (over 2.0), and their difficulty estimates were reasonable. Conclusion The M-BDDQ-AS is a reliable and valid self-reported questionnaire that can be used in rhinoplasty patients. The very good psychometric validation of the M-BDDQ-AS indicates that it can be used in clinical practice and scientific research. Graphical Abstract